PENGARUH PERTUMBUHAN PERUSAHAAN DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS DAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL INTERVENING: Studi Empiris Perusahaan Manufaktur di BEI Tahun 2012-2016 - Fatiyah, Nur; Sulistiyo, Heru; Sam’an, Sam’an (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2018)
This research is about the value of manufacture company in Indonesian stock exchange from 2012 until 2016. The purpose of this research is to analyze profitability, and good corporate governance in mediating the influence of company growth and capital structure to firm value. The sample is selected through purposive sampling as many as 46 manufacturing companies in Indonesian stock exchange. The data obtained by analyzing the company's financial statements of the year 2012 to 2016. Data analysis is using multiple linear regression with SEM-PLS 4.0 program. The result showed that company growth has a significant positive effect to profitability, capital structure has positive effect not significant to profitability. The company growth has a negative effect not significant to good corporate governance, capital structure has positive effect not significant to good corporate governance. The company growth has positive effect not significant to firm value, capital structure has negative effect not significant to firm value. Profitability, and good corporate governance have a significant positive effect on firm value. Profitability mediates the influence of company growth, and the capital structure to firm value. Good corporate governance does not mediate the effect of company growth, and the capital structure to firm value, good corporate governance mediates the influence of capital structure to firm value.